Peningkatan Kompetensi Usaha Mikro Kecil dan Menengah (UMKM) Berbasis Analisa Studi Kelayakan Bisnis - Pratama, Bima Cinintya; Bagis, Fatmah; Retnaningrum, Maharani; Innayah, Maulida Nurul (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2019)
The doers of micro small medium enterprises (UMKM) of Subdistrict Branch Office of Aisyiyah (PCA) in North Purwokerto have limited understanding and skills in the evaluation of management performance and financial management. These activities aim to improve the competence of the doers of micro small medium enterprises (UMKM) of PCA in North Purwokerto on the business development based on business feasibility study. The participants joining the accompaniment of the evaluation of management performance and financial management competence were 24 people. The methods used in the accompaniment were theory exposure and case study, business consultation, and the practice of the formulation of business feasibility study-based enterprises in groups. The results of the accompaniment show that the knowledge of the doers of micro small medium enterprises (UMKM) on the aspect of management and finance based on the business feasibility study improves.